The Effect of Total Physical Response Method on Students' Speaking Skill at Elementary School - Nirma, Nirma; Saiful, Saiful; Nappu, Syamsiarna (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
The Effect Of Total Physical Response (TPR) Method On Students’ Speaking Skill at Elementary School. The main problem of this study is the lack of students' speaking ability, especially in English, so the researchers sought ways to improve students' pronunciation accuracy and vocabulary after applying the Total Psychal Response (TPR) method at Lab School SD Unismuh Makassar. This study used a quantitative quasi-experimental design by applying the TPR method to see its effect on students' speaking ability. The procedure of this research includes pre-test, treatment, and post-test. The samples in this study were second grade students of Lab School SD Unismuh Makassar consisting of two classes which became the population. This research used total sampling technique. The instruments of this research are speaking tests and recording devices. So in this study, speaking test was used as a test instrument to collect data. Based on the results of the study, the pre-test score in the experimental class in pronunciation accuracy was (22.72) and the post-test score was (65.90). and the pre-test score on vocabulary was (24.99) and the post-test score was (76.51). Meanwhile, the pre-test score in the control class in pronunciation accuracy was (24.99) and the post-test score was (33.33). and the score on vocabulary was (21.96) and the post-test score was (42.42). Based on hypothesis testing, it shows that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected based on hypothesis testing. The results showed that in the experimental class there was a significant increase from pre-test to post-test using the TPR method compared to the results of the control class using the TBLT method. So, it can be concluded that the use of TPR method can affect students' speaking ability in terms of accuracy of pronunciation and vocabulary at the laboratory school of SD Unismuh Makassar.